Clinical ethics between theory and praxis - Galvagni, Lucia (Medicina e Morale, 2024)
Clinical ethics is an important area of bioethics that deals with ethically complex clinical cases and situations. Beginning with a brief historical reconstruction, the article presents the characteristics of the discipline and the practice of ethical consultations, reflecting on the methodologies and contribution of ethics in the clinic, in the light of some training experiences, centered on the review of cases a posteriori, to highlight how juxtaposing different languages can also help to advance different readings and interpretations in complex care situations and scenarios.